Copenhagen hip and groin outcome score (HAGOS) in male soccer: reference values for hip and groin injury-free players. Issue 7 (12th July 2013) - Thorborg, Kristian; Branci, Sonia; Stensbirk, Frederik; Jensen, Jesper; Hölmich, Per
Abstract : Background/aim: Reference values are needed in order to interpret the Copenhagen Hip and Groin Outcome Score (HAGOS) in male soccer players with hip and groin pain. The aim of this study was to establish reference values for HAGOS in hip and groin injury-free male soccer players. Methods: We included 444 groin injury-free soccer players from 40 clubs (divisions 1–4) in Eastern Denmark, mean age (SD) 23.6 (4.4), training soccer 3.4 (1) times per week. All players were hip and groin injury-free at the time of inclusion (beginning of season, 2011). Results: Of the 444 hip and groin injury-free players, 301 reported no hip and/or groin pain in either the present or the previous season, and 143 reported that they had experienced hip and/or groin pain in the previous season. Players (n=143) with hip and groin pain in the previous season displayed lower scores than players without (n=301), for all HAGOS subscales (p<0.001). Age and playing level were not related to HAGOS. The 95% reference ranges for HAGOS subscales in hip and groin injury-free soccer players, with no pain in the previous or present season (n=301), are: pain: 80.1–100, symptoms: 64.3–100, activities of daily living: 80.3–100, sport and recreational activities: 71.9–100, participation in physical activity: 75–100 and quality of living: 75–100. Conclusions: Lower HAGOS subscales are seen in soccer players who have experienced hip and/or groin pain in the previous season, compared with those who have not. Median HAGOS subscale scores in hip and groin injury-free soccer players are in proximity to the maximum score (100 points).